MULTIPLICITY OF CRIMES IN INDONESIAN LAW: REGULATION AND DETERMINATION OF CONCURSUS REALIS - Rannu, Delycia Anwar; Adhari, Ade (Jurnal Al-Dustur, 2025)
Concursus realis, or the accumulation of criminal acts, is crucial because it ensures that multiple offenses committed by the same individual are properly addressed within the judicial system. Indonesia, as a state governed by law as stipulated in Article 1 paragraph (3) of the 1945 Constitution, upholds justice and legal certainty as the primary principles of its penal system. This study aims to analyze the regulation of concursus realis in Indonesian criminal law and its application in court rulings. The research employs normative legal methods with a statutory and case analysis approach, utilizing secondary data from regulations, doctrines, and jurisprudence, which are analyzed. The findings reveal that concursus realis is regulated under Articles 65 and 66 of the Indonesian Penal Code (KUHP) and Articles 58 and 59 of Law No. 1 of 2023, stipulating cumulative penalties for independent criminal acts within a series of events, with the maximum sentence of the most severe offense increased by one-third. The application of concursus realis in judicial practice shows significant variation, influenced by judges' interpretations of the 'series of events' concept, yet often inconsistent due to the lack of technical guidelines. Therefore, regulatory revisions and the harmonization of interpretations are essential to ensure that the application of concursus realis supports the realization of justice and legal certainty.